2019
DOI: 10.1152/ajpgi.00148.2018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble epoxide hydrolase ameliorates hyperhomocysteinemia-induced hepatic steatosis by enhancing β-oxidation of fatty acid in mice

Abstract: Hepatic steatosis is the beginning phase of nonalcoholic fatty liver disease, and hyperhomocysteinemia (HHcy) is a significant risk factor. Soluble epoxide hydrolase (sEH) hydrolyzes epoxyeicosatrienoic acids (EETs) and other epoxy fatty acids, attenuating their cardiovascular protective effects. However, the involvement of sEH in HHcy-induced hepatic steatosis is unknown. The current study aimed to explore the role of sEH in HHcy-induced lipid disorder. We fed 6-wk-old male mice a chow diet or 2% (wt/wt) high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…sEH expression increases in several diseases, 9,[20][21][22] which in turn decrease several important biological EpFAs. EET are biologically active metabolites of AA, generated by cytochrome p450s (CYP).…”
Section: Discussionmentioning
confidence: 99%
“…sEH expression increases in several diseases, 9,[20][21][22] which in turn decrease several important biological EpFAs. EET are biologically active metabolites of AA, generated by cytochrome p450s (CYP).…”
Section: Discussionmentioning
confidence: 99%
“…EETs may potently downregulate endoplasmic reticulum (ER) stress responses as demonstrated in response to cigarette smoke damage ( Yu et al, 2015 ). Thus, inhibition of sEH may allow for their stability and prolonged effects and has demonstrated pro-resolution activity such as stimulation of SPMs and activating anti-cytokine programs in multiple inflammatory diseases, including those which are risk factors for cancer induction ( Schmelzer et al, 2005 ; Wang et al, 2018 ; Yao et al, 2019 ; Yu et al, 2015 ). Importantly, the sEH eicosanoid pathway has been suggested to be involved in the progression of colorectal cancer, including obesity-associated cancer ( Zhang, Sanidad, & Zhang, 2019 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In animal models of CBS deficiency, the enhanced oxidative stress and hepatic lipid accumulation are observed [102] . Namekata et al proposed that the abnormal metabolism in the liver from CBS knockout mice may be induced by hyperhomocysteinemia [102] , which is a risk factor for hepatic steatosis [103] . Furthermore, the same group further demonstrated that the damaged β-oxidation of fatty acid and thiolase activity, and the aberrant levels of very low density lipoprotein (VLDL) are major contributing factors for hepatic steatosis in CBS knockout mice [102] .…”
Section: Role Of H 2 S In Non-alcoholic Fatty Livementioning
confidence: 99%